POSSIBLE MECHANISMS UNDERLYING BACTERIAL-VIRAL INTERACTIONS IN RESPIRATORY DISEASES: A REVIEW - Oluwayelu, Daniel Oladimeji; Adebiyi, Adebowale Idris (African Journal of Infectious Diseases (AJID), 2015)
Background: Respiratory diseases are frequent and economically significant problems in both humans and animals. The potential losses resulting from decrease in average daily gain and feed efficiency, as well as the cost of preventing or treating these diseases are substantial. Although synergistic relationships between bacteria and viruses have been documented to aggravate these diseases, the pathogenic mechanisms remain poorly understood. Materials and method: For this review, PubMed and Google search engines were used to select about 45 publications on bacterial-viral interactions in respiratory conditions. Studies on animal models were also included in the review. The publications were compared and summarized using a narrative review approach and findings were described qualitatively. Results: Respiratory diseases are exacerbated by interactions between bacteria and viruses in both humans and animals. Possible mechanisms underlying this synergism were found to include, among others, increased bacterial adherence due to viral infection, reduction of mucociliary clearance, diminished chemotaxis, immature phagocytes and decreased surfactant levels. Conclusion: Interactions between bacteria and viruses make management of respiratory diseases difficult. However, exploration of the highlighted mechanisms responsible for this synergism in the development and production of novel antimicrobials and vaccines against these pathogens is crucial to improving management, prevention and control of respiratory infections. This may be particularly beneficial in this era of increasing antibiotic resistance.